(Budget Governance in Libya (2017–2025): An Applied Analytical Study of Its Principles and Dimensions) (Al-Farooq Journal of Sciences, 2026)
This study examines the principles of budget governance in Libya during the period 2017–2025, relying on recent national and international financial data. The research employs a theoretical framework that defines fiscal governance principles as articulated by leading institutions such as the IMF, World Bank, and OECD, including transparency, comprehensiveness, fiscal discipline, efficiency, sustainability, and accountability. These principles were tested within the Libyan context through quantitative and qualitative analysis of financial data and institutional reports. The findings indicate that Libya’s public budget falls short of meeting most of these principles. Transparency is undermined by the absence of final accounts and delayed data publication; comprehensiveness is weakened by off-budget expenditures; and fiscal discipline is constrained by heavy dependence on oil revenues. Moreover, efficiency is compromised by the predominance of recurrent spending over investment, sustainability is limited due to the absence of medium-term planning, and political fragmentation and weak oversight bodies hamper accountability. The study concludes that the lack of fiscal governance reflects a deep institutional crisis that undermines economic stability and sustainable development. It recommends comprehensive legislative and institutional reforms, including revenue diversification, the adoption of performance-based budgeting, and strengthening oversight independence in line with international best practices.
Keywords: Principles of Budget Governance, Fiscal Governance, Public Budget, Transparency, Fiscal Discipline